Malaria Prophylaxis During Pregnancy In Primigravidae Using Sulfadoxine/pyrimethamine In Wad Medani-Sudan - Suleiman, Imad Eldin Elgack; A/Alla Mohamadani, Ahmed; Mirgani, Omer Ahmed; Mohamed Nour, Bakri Yousif (Gezira Journal of Health Sciences, 2004)
Objectives: (I)To evaluate the efficacy of Sulfadoxine/pyrimethamine as a prophylactic intervention in prevention and control of malaria during pregnancy;(II) to compare effect on neonatal low birth weight (LBW) between  intervention and control groups; (III) to determine the proportion of maternal, neonatal and placental parasitaemia among intervention control groups. Material and methods: A prospective case/control interventional study of 113 primigravidae, 57 as a intervention group and 56 as a control group selected through a cluster sampling technique. After taking their verbal consent, the intervention group received two doses of sulfadoxine/pyrimethamine (SP) in the second and early third trimesters, and followed up according to the WHO antenatal care schedule. The outcomes include the following: (I) Reduction of malaria episodes during pregnancy in primigravidae ; (II) reduction of prevalence of neonatal low birth weight; and (III) determination of the prevalence of maternal, neonatal and placental parasitaemia. Results: The frequency of malaria episodes during pregnancy in primigravidae was found to be 14.6% and 29.7% for intervention and control groups respectively and there was a significant statistical difference between the two groups (P< 0.00001). The proportion of LBW was found to be 3.5% and 35.8% for the intervention and control groups respectively and there was a significant statistical difference between the two groups (Z=6.99). The proportion of maternal, neonatal and placental parasitaemia was found to be (10.9% and 54.9%),(11.1% and 54.9%) and (24% and 50%) for intervention and control groups respectively and there was a significant difference between the two groups regarding maternal and neonatal parasitaemia, while there was no significant difference regarding placental parasitaemia.